2010
DOI: 10.1016/j.physbeh.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent activity-based anorexia increases anxiety-like behavior in adulthood

Abstract: Activity-based anorexia is a paradigm that induces increased physical activity, reduced food intake, and heightened activity of the hypothalamic-pituitary-adrenal axis in adult rats. To investigate whether experience with activity-based anorexia produced enduring effects on brain and behavior, female adolescent rats experienced activity-based anorexia during adolescence and were tested in adulthood for anxiety-like behavior on an elevated plus maze and in an open field. Analysis of elevated plus maze and open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 54 publications
2
34
1
Order By: Relevance
“…Similarly, plasma corticosterone, the main rodent glucocorticoid, is elevated in animals undergoing the ABA protocol [80]. A history of ABA exposure during adolescence has been shown to have long-term influence on anxiety-like behavior and neuroendocrine measures of HPA axis activation in adult female rats that have returned to a normal body weight [66]. These animals demonstrated persistent elevations in plasma corticosterone and…”
Section: Exercise and Caloriementioning
confidence: 99%
“…Similarly, plasma corticosterone, the main rodent glucocorticoid, is elevated in animals undergoing the ABA protocol [80]. A history of ABA exposure during adolescence has been shown to have long-term influence on anxiety-like behavior and neuroendocrine measures of HPA axis activation in adult female rats that have returned to a normal body weight [66]. These animals demonstrated persistent elevations in plasma corticosterone and…”
Section: Exercise and Caloriementioning
confidence: 99%
“…During the acquisition trial there were no significant differences between ABA and SED rats in the total time spent exploring an object (t(15)=0.902, df=8, p=0.382). The rats did not display a clear preference for either object (Chi-Square=7.228, df=8, p=0.370).…”
Section: Resultsmentioning
confidence: 91%
“…The rats did not display a clear preference for either object (Chi-Square=7.228, df=8, p=0.370). During the novel object recollection trial, no statistical differences in total time spent exploring an object were observed (t(15)=1.618, p=0.126). However, ABA rats spent significantly less time exploring the novel object compared to SED rats (t(15)=−4.831, p<0.001).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations